2020
DOI: 10.1097/qad.0000000000002546
|View full text |Cite
|
Sign up to set email alerts
|

Performing rapid autopsy for the interrogation of HIV reservoirs

Abstract: Rapid autopsy at the end of life in people with HIV (PWH) permits the preservation of valuable tissue specimens for subsequent study of HIV reservoirs. At our institution, we have developed a cohort of PWH who consent to a rapid autopsy to gather a wide range of fluids and tissues with the goal of advancing HIV cure research. The protocol for successfully performing these autopsies has required careful thought and development over months and years. We have now successfully performed six rapid autopsies and det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…The ability of HIV to infect both T cells and macrophages allows the virus the potential to establish reservoirs in both cell types. This provides benefits for HIV to establish reservoirs in macrophages with long half-lives that can sustain viral replication for several months just like in T cells, as was explained recently in mice and SIV-infected macaques study (57).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The ability of HIV to infect both T cells and macrophages allows the virus the potential to establish reservoirs in both cell types. This provides benefits for HIV to establish reservoirs in macrophages with long half-lives that can sustain viral replication for several months just like in T cells, as was explained recently in mice and SIV-infected macaques study (57).…”
Section: Discussionmentioning
confidence: 79%
“…However, the role of resident viral reservoirs is currently still under investigation. In addition, most data are obtained from post mortem tissues or small samples from biopsies or tissue donations, which provides us a small and insufficient window to observe HIV behavior in tissues (36,39,57,58). Several studies showed that lymphoid tissues (such as the spleen, thymus, and GALTs as well as compartmentalized tissues such as the brain) have viral reservoirs and viral DNA can be recovered (58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%
“…We developed a decision tree for testing deceased participants for SARS-CoV-2 to minimise risk of spread (figure 1). i By May 2020, we were able to conduct limited study visits with participants and converted many surveys and check-ins to i We drafted new protocols for performing the rapid research autopsy: a non-COVID-19 autopsy would be done following normal protocols 22 except the lungs, the organs with the highest risk of viral particles and highest potential for aerosolisation, would be processed last to minimise exposure to the study team. In a COVID-19 autopsy, only two medical doctors with fittested, approved N95 masks would process tissues by sealing them in transportation containers in the morgue and decontaminating the outside of these containers.…”
Section: Issues Relevant To Healthcare Research Conducting Research I...mentioning
confidence: 99%
“…The containers would then be transported across the street to laboratory facilities equipped with biosafety cabinets and, there, the tissue would be processed for flash-freezing. Tissue collection was reduced by approximately 33% in a COVID-19 rapid research autopsy to stay within the prescribed 6-hour time limit 22…”
mentioning
confidence: 99%
“…Using blood and tissue samples collected before and after death from six Last Gift study participants, Chaillon and colleagues found that HIV persists in blood cells and across 28 deep tissues including cardiovascular, gastrointestinal, and lymphoid tissues [ 6 ]. Rawlings et al developed a rapid research autopsy protocol to guide the collection of fluids and tissues for interrogating HIV reservoirs [ 7 ].…”
Section: Introductionmentioning
confidence: 99%